Human occupation of Northern Europe in MIS 13: a response to comments by Gibbard et al. (2019). (1st November 2019) - Lewis, Simon G.; Ashton, Nick; Hoare, Peter G.; Parfitt, Simon
Abstract: In a recent paper (Lewis et al., 2019 ) we reported the results of geological and archaeological investigations at Happisburgh Site 1. We also considered the significance of the site for understanding the human occupation of northern Europe during the early Middle Pleistocene. In a comment on the paper, Gibbard et al. (2019) raise a number of issues concerning lithostratigraphic terminology, the age of the deposits at Site 1, and the wider regional context of the Site 1 archaeological assemblage. Here we respond to Gibbard and colleagues' objections and, in particular, we present evidence in support of our contention that the Palaeolithic assemblages from the Breckland sites of Warren Hill and High Lodge pre-date the Anglian (MIS 12) glaciation and may be considered to date to MIS 13.